P-005 A novel three-dimensional (3D) revascularization device: histopathology results from a rabbit model and early clinical experience with the penumbra separator 3D. (4th July 2012) - Weber, J; Jansen, O; Rohr, A; Knauth, M; Schramm, P; Grand, M; Weber, W; Loehr, C; Doerfler, A; Struffert, T; Goelit, P; Zimmer, C; et al.
Abstract : Introduction/Purpose: We report on the histopathology results from a preclinical rabbit study and our early clinical experience with the Separator 3D device, featuring novel 3D chambers for securing and removing thrombus. Compatibility with differently sized catheters provides flexibility to combine with aspiration. Materials and Methods: To evaluate vascular responses of multiple 3D deployments and resheathings, a rabbit elastase model study examined right and left subclavian arteries from five rabbits 30 days after eight cycles. Vessels were subjected to histopathology analysis. Case experience in six European centers was collected in the first 30 days post-device approval. Fourteen consecutive patients presenting with acute ischemic stroke within 8 h of symptom onset were treated with the 3D device. Five cases involved ICA to MCA (M1 or M2) occlusion; four involved M1 segmental occlusion; two involved M1 to M2 occlusion; one involved basilar to PCA occlusion; two were excluded due to underlying stenosis. In the two cases involving stenosis, use of the 3D device followed by other stent retrievers like Solitaire (Covidien), Trevo (Stryker), and Restore (Reverse Medical) could not achieve revascularization; they were eventually resolved by balloon or stent. Results: Multiple 3D deployment and resheathing cycles in the rabbit revealed no histopathologic lesions at 500 μm magnification nor evidence of injury or inflammation in the internal elastic lamina. Notably, no intraluminal fibrin or thrombus was found. In a multi-center case review study, the 3D device achieved 92% revascularization to TICI 2B or 3, excluding stenotic cases. In all cases, the 3D was successfully delivered to the occlusion site resulting in successful recanalization with 1.5 average passes. No vessel injury, vasospasm, or embolization of new territory was observed. Conclusion: Preliminary results demonstrate that the Penumbra Separator 3D is a safe, effective revascularization device. Early animal and clinical experience with the 3D device appears promising. Absence of vessel injuries or new territory emboli may be aided by intraluminal 3D chambers that engage and remove clot with aspiration applied close to the lesion site. Smooth delivery and easy handling of the 3D was noted even in highly tortuous anatomy. Further case experience is warranted to confirm these promising initial observations. Competing interests: None.